Why Biblical Arguments for Abortion Fail - Miller, Calum (Christian bioethics, 2023)
While the traditional Christian teaching opposing abortion has been relatively unanimous until the twentieth century, it has been claimed in more recent decades that certain Biblical passages support the view that the fetus, or unborn child, has a lesser moral status than a born child, in a way that might support the permissibility of abortion. In this paper, I address the foremost three texts used to argue this point: Genesis 2:7; Exodus 21:22-25; and Numbers 5:11-31. I argue that interpreting the former in the literal way necessary to support abortion leads to untenable moral and exegetical conclusions, indeed straightforwardly contradicting other Biblical texts. I then demonstrate that the most plausible readings of the other passages—on textual and contextual grounds—do not support a lesser moral status, one of the passages plausibly even supporting full moral status, for the unborn child.